Intertextuality in the Regent Theatre Script by Dede A. Majid - Eka Gusti Triana; Alis Triena Permanasari; Giri Mustika Roekmana (CV. Edujavare Publishing, 2026)
In the context of literary studies, this openness of meaning shows that dramatic texts do not stand autonomously, but are always in a network of relations with other texts. This study aims to analyze the forms, patterns, and functions of intertextuality in the theatrical script Regent by Dede A. Majid. It employs a qualitative descriptive method with a text analysis approach based on Julia Kristeva’s theory of intertextuality, supported by the ideas of Roland Barthes and Gérard Genette. The findings reveal that intertextuality appears in the forms of allusion, quotation, transformation, and adaptation, with dominant patterns of transformation and opposition toward colonial discourse. Its functions include aesthetic, semantic, social critique, and ideological roles that construct meaning dialogically. The study confirms that Regent reconstructs and critiques colonial historical narratives. This research contributes to the development of intertextuality studies and strengthens the study of Banten regional literature.